Acute Effects of Particulate Air Pollution on Ischemic Stroke and Hemorrhagic Stroke Mortality - Zhang, Runhua; Liu, Gaifen; Jiang, Yong; Li, Gang; Pan, Yuesong; Wang, Yilong; Wei, Zaihua; Wang, Jing; Wang, Yongjun (Frontiers in Neurology, 2018)
Background and Purpose Most of studies reported the association of particulate matter (PM) with stroke are originated from high-income countries. Few studies have examined the association between PM and stroke in middle- and low-income countries and considered the subtypes of stroke. In this study, we examined the short-term effects of particulate matter < 2.5 μm in diameter (PM2.5) and particulate matter < 10 μm in diameter (PM10) on ischemic stroke mortality and hemorrhage stroke mortality in Beijing, China. Methods We used quasi-Poisson generalized additive models to evaluate the association of PM2.5 and PM10 and cerebrovascular diseases mortality, as well as ischemic stroke mortality and hemorrhage stroke mortality. In the model, we controlled long-term and season trends, temperature, and relative humidity, day of week and air pollution. For cerebrovascular diseases mortality, we examined the effects stratified by sex and age with different lag days. Results A total of 48,122 deaths for cerebrovascular disease (32,799 deaths for ischemic stroke and 12,909 deaths for hemorrhage stroke) were included in the study. PM2.5 was associated with stroke mortality. The increase of 0.27% (95% CI, 0.12%-0.43%), 0.23% (95% CI, 0.04%-0.42%) and 0.39% (95% CI, 0.09%-0.70%) were estimated for cerebrovascular diseases, ischemic stroke and hemorrhage stroke mortality with 10 μg/m3 increase of PM2.5, respectively. For PM10, the associations were also detected for cerebrovascular diseases and ischemic stroke, whereas no association was observed with hemorrhage stroke. Stratified analysis suggested age and gender did not modify the effects significantly. Conclusions Our study suggested that short-term exposure to ambient PM may increase the risk of stroke.